2024
DOI: 10.1051/0004-6361/202346800
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy morphology from z ∼ 6 through the lens of JWST

M. Huertas-Company,
K. G. Iyer,
E. Angeloudi
et al.

Abstract: The James Webb Space Telescope's (JWST's) unprecedented combination of sensitivity, spatial resolution, and infrared coverage has enabled a new era of galaxy morphology exploration across most of cosmic history. We analyze the near-infrared (NIR $ rest-frame morphologies of galaxies with $ M_*/M_ in the redshift range of $0<z<6$, compare with previous HST-based results and release the first JWST-based morphological catalog of $ galaxies in the CEERS survey. We classified the galaxies in our sample into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…In light of recent developments, our view of disk formation in the early Universe is undergoing a radical overhaul. With the launch of the James Webb Space Telescope (JWST), a new window into the distant Universe has revealed that (mostly thin) disk galaxies 5 dominate the population out to at least z ≈ 6 (Ferreira et al 2023;Kartaltepe et al 2023;Robertson et al 2023), although further analysis is needed (Huertas-Company et al 2024). We can use bars (and bulges) to learn about the early history of galaxies, particularly when the phenomenon can be traced to the highest redshifts.…”
Section: Introductionmentioning
confidence: 99%
“…In light of recent developments, our view of disk formation in the early Universe is undergoing a radical overhaul. With the launch of the James Webb Space Telescope (JWST), a new window into the distant Universe has revealed that (mostly thin) disk galaxies 5 dominate the population out to at least z ≈ 6 (Ferreira et al 2023;Kartaltepe et al 2023;Robertson et al 2023), although further analysis is needed (Huertas-Company et al 2024). We can use bars (and bulges) to learn about the early history of galaxies, particularly when the phenomenon can be traced to the highest redshifts.…”
Section: Introductionmentioning
confidence: 99%
“…However, the recent multiband images from the JWST/NIRCam have dramatically altered our understanding of the galaxy morphology of distant galaxies. An increasing body of evidence now suggests that these galaxies are predominantly disk dominated (Ferreira et al 2022(Ferreira et al , 2023Kartaltepe et al 2023), and remarkably, the Hubble sequence is observable even at z = 6 (Huertas- Company et al 2024). These most recent findings underscore the necessity to reassess the evolutionary trend in morphological structures of galaxies across different rest-frame wavelengths and redshifts.…”
Section: Introductionmentioning
confidence: 99%